The Approach of the European Union Towards China’s Violation of Human Rights - Březinová, Klára (2021)
Human rights are one of the core values of the European Union from its early start. It equally binds itself to promote and protect human rights while dealing with third party states on the international level. Therefore, the thesis aims to examine the EU’s position regarding China’s human rights abuses. Especially within its foreign policy approach. As the theoretical background constructivism, namely Nicolas Onuf’s conception was used. For the practical part, discourse analysis was used. Through three official discourses and two dialogues, the thesis tries to understand the application of the European policies in praxis. The chosen actors of the EU foreign policy were The President of the EC, Ursula von der Leyen and the Vice President of the EC and simultaneously the High Representative of the EU, Josep Borrell Fontelles. In the practical part, there have been analysed three discourses where the actors directly represent the EU at a press conference or as in the case of the President of the EC, once in front of the EP. For the High Representative of the EU, Borrell, there were furthermore added two discourses from dialogues held at external conferences. After presenting Onuf’s conception of constructivism, which the thesis is based on and the contextualisation of the actors’ role within the EU foreign affairs. The thesis briefly presents human rights issues in China and the official approach of the EU towards human rights abuses. The chosen China human rights issues are tackling the Nort-West province Xinjiang and digital freedom connected to the 5G communication. The EU stances are mostly derived from the EU official documents such as the ECHR, the Lisbon Treaty, European Action Plans and others. The biggest contribution of the thesis is incorporated in the fourth, respectively the fifth chapter.